PENGARUH MODEL PEMBELAJARAN INKUIRI BERBASIS PROYEK TERHADAP KETERAMPILAN PEMECAHAN MASALAH PESERTA DIDIK FASE E DI SMAN 1 PADANG - Permata Sari, Rovi; Arsih, Fitri; Alberida, Heffi; Olvia Rahmi, Fitri; Aulia Fikri, Refsya (Universitas Cokroaminoto Palopo, 2024)
Problem solving ability is the ability of learners to use their own thinking process to solve problems by gathering facts, analysing information, summarising various alternative solutions, and choosing the most effective solution to the problem. The results of the preliminary study of the problem solving skills of phase E students of SMAN 1 Padang are still in the category that needs improvement and the category that is lacking. One of the efforts to improve problem solving skills can be done by applying a project-based inquiry learning model. The purpose of this study was to determine the effect of project-based inquiry learning model on problem solving skills of phase E students at SMAN 1 Padang. This research is a quasi experiment with pretest-posttest control group design. The population in the study was phase E students of SMAN 1 Padang. Sampling was done by purposive sampling technique. The results of the study obtained data on the value of problem solving skills of experimental class students higher than the control class. The results of hypothesis testing get the results of sig value < 0.05 which is 0.000 so it can be concluded that the project-based inquiry learning model has a positive effect on the problem solving skills of phase E students at SMAN 1 Padang on environmental change material.